Analisis Laba Usaha UMKM Warung Seblak Teh Idah di Desa Pancakarya Kecamatan Tempuran - Anggi Ramadani; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research focuses on the UMKM of the Seblak Teh Idah stall in Pancakarya Village, Tempuran District, Karawang Regency. This research is to analyze the business profits of Seblak Teh Idah UMKM which have survived for 10 years from starting in 2013 until 2022. The method used in the research is descriptive quantitative, research activities at Seblak Teh Idah UMKM for 3 months, starting from 1 september 2023 to January 31 2024. The researcher's aim is to analyze operating profits at the Seblak Teh Idah UMKM stall and to analyze the development of profit results. business at the Seblak Teh Idah stall. Because there is one of the problems in the Idah seblak tea business, how to manage profits from sales revenue well, because the seblak business still survives today and is growing. Research result show that Seblak Teh Idah UMKM have experienced developments in their business such as more comfortable facilities, additional cooking utensils, eating utensils and additions to the menu. The profits from the seblak Teh Idah stall business have brought changes to the family's business and economy and have started to show very good development.